“Las acciones pastorales del Obispo Alejandro Labaka en los pueblos indígenas del cantón Francisco de Orellana”. - Granda Moreno, Anderson Xavier (2018)
This project analyzes the incidence of the pastoral actions of Bishop Alejandro Labaka in the indigenous towns of Francisco de Orellana canton. Throughout this study it is noted that the mission of the Order of the Capuchin Minor Brothers continues with the legacy of the Bishop who fought for the human and territorial rights of the indigenous towns of the Ecuadorian Amazon. In the first chapter the missionary work of Bishop Alejandro Labaka is studied. The analysis has three moments: in the first moment his family life and his entrance to the seminary are described. In a second moment the mission in Pingliang is studied. A third moment is part of the study of the mission in Ecuador, the apostolic prefecture of Aguarico. The second chapter analyzed the historical trajectory of the indigenous cultures of Francisco de Orellana and the motivations of the Capuchin mission of Alejandro Labaka. The third chapter deals with the pastoral actions of Alejandro Labaka for the benefit of indigenous communities. The fourth and final chapter explores the social, political and cultural implications of the Amazonian indigenous towns, as well as the starting point for the experiences of the political and social participation of missionary campaigns and indigenous organizations. The research work is qualitative. In the development of the exploration, the Inductive Hypothetical method was used, documentary and bibliographic research were applied. Field research was developed. To obtain the information, the interview technique was used.